No difference between CT- and MRI-based patient-specific instrumentation for total knee arthroplasty: an updated systematic review and meta-analysis - Shao, Long; Wu, Xiang-Dong; Liu, Yuhao; Wang, Xing; Li, Chunyan; Tao, Kun; Wang, Shicheng (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectOur previous systematic review of either computed tomography (CT)-based or magnetic resonance imaging (MRI)-based patient-specific instrumentation (PSI) systems in total knee arthroplasty (TKA) included literature up to June 2016. However, the quickly evolving field warranted an update. Therefore, the aim of this systematic review and meta-analysis was to provide updated, evidence-based insights comparing the outcomes of CT-based versus MRI-based PSI systems in TKA.MethodsWe conducted comprehensive searches of PubMed, Embase, and the Cochrane Library databases from inception to February 2025. Prospective comparative trials that compared CT-based versus MRI-based PSI systems for TKA were included. Our predefined primary outcome was the incidence of outliers in overall coronal limb alignment. Secondary outcomes encompassed the accuracy of component alignment, operation time, and clinical outcomes.ResultsNine publications reporting seven eligible trials were identified. Six trials involving a total of 407 knees were included for qualitative analysis, with five trials suitable for quantitative meta-analysis. The integrated results revealed no significant differences between CT- and MRI-based PSI systems concerning the outlier incidence of coronal overall limb alignment, the outlier incidence of coronal/sagittal alignment of the femoral/tibial component, the angular errors of coronal overall limb alignment, the angular errors of the femoral/tibial component in the coronal plane, or incidence of change of implant size of the femoral/tibial component. However, CT-based PSI systems were associated with significantly greater angular errors in coronal limb alignment (mean difference [MD]: 0.69°; 95% CI, 0.03°–1.36°; P = 0.04) and a prolonged operative time (MD: 5.02 min; 95% CI, 1.26min–8.79 min; P = 0.009) when compared to MRI-based systems. Clinical outcomes, while not amenable to meta-analysis due to clinical heterogeneity, showed no significant differences between groups during short-to mid-term follow-up.ConclusionThis finding is inconsistent with our previous study. Contrary to our previous findings, current evidence indicates no significant difference in alignment outcomes between CT-based and MRI-based PSI systems for TKA. Additionally, short-to mid-term clinical outcomes were comparable between the two imaging modalities.Systematic Review Registrationidentifier CRD42022339910.